Kontekstualisasi Marari Sabtu Sebagai Jembatan Misi Injil Terhadap Parmalim - Rafles P. Sabbat; Stimson Hutagalung; Rolyana Ferinia (Media (Jurnal Filsafat dan Teologi), 2022)
The essay deals with the so-called Marari Sabtu in the Parmalim tradition as a bridge for the Christian mission to Parmalim followers. The starting point is the fact of similarity in terms of worship day between the Parmalim tradition and the biblical testimony, namely the observance of Sabbat. Parmalim observes the tradition of “Marari Sabtu”, which is a weekly worship ceremony to worship Debata Mulajadi Nabolon, and worship takes place every Saturday. The research question is: Can the similarity in terms of worship day be a bridge for evangelism for Permalim followers? This paper shows that Paul's method to the Athenians can be a model for evangelization efforts for Parmalins. It means that an effort to contextualize faith can be carried out for Parmalim followers by starting from the Marari Sabtu tradition.